Informatics and Social Action Funds in SubSaharan Africa - Pidatala, Krishna (World Bank, Washington, DC, 2012)
The note outlines the impact of three of the largest Bank-assisted social action funds in Sub-Saharan Africa, and the role the informatics component of each of these funds (Ethiopia, Malawi, and Zambia), played in the dynamics of project implementation. Lessons highlight the significance of informatics as a development tool, particularly in the design, and implementation of social funds. However, due to the diverse geographical nature of these social action funds, technical expertise was spread too thin at the regional levels, contributing to ineffective results in information technology, consequently with increased costs in time, and resources.